Analysis of human bones from I century A. D. from greek-roman necropole in Gabbari (Alexandria) - Dzierżykray-Rogalski, Tadeusz; Promińska, Elżbieta (Anthropological Review, 1977)
Use of the necropole has been started in the end of IV century B.C. and completed in VII century A.D. During enlargement of the port in Alexandria in XIX century the necropole has been partly destroyed. Excavation of the site was started in 1974 by professor G. Grimm from University of Trier (BRD) acting for German Institute in Cairo. In 1975 during exploration of burial crypts skeletal material has been obtained. The material was transferred to Polish Center for Mediterranean Archeology where in March of 1976 anthropological examination was carried by professor T. Dzierżykray-Rogalski and docent E. Promińska.All preserved bones were mixed post-mortem, some of them were in bad condition and not too numerous. The material comprises remains of five males. three females and eight children. All examined males were old ones (youngest 50 - 60 and oldest 65 - 75 years old at death). Age estimation of females was possible in two cases only (20 and 40 - 50 years). Most of the children have died in the age of approximately 2.5 years.The material is too fragmentary to allow extensive demographic analysis, though high age attained by males is noteworthy. All the males belonged to the white racial stock and were characterized by robust body build with probably high stature.Observed pathological changes are worth of attention. It were found deformations of bones of type of spondylosis, arthrosis deformans and osteoporosis, In one case dental caries was present. The changes of these types were observed by the authors on other materials from Alexandria — Moslem necropoles on Kom El Dikka. Although the groups differ ethnically and had lived in different times and under diverse social and economic conditions they must be subjected to the same geographic environment resulting in highly analogous pathological changes observed.